Associations of healthy lifestyle and family income to poverty ratio with all-cause mortality among people with prediabetes and diabetes: a prospective cohort study - Zhu Li; Lin Zhou; Yongshi Wu; Tao Ding; Yuxin Gan; Xiang Fan (BMC Public Health, 2025)
Abstract Background Family income to poverty ratio (PIR) may have independent effects on diet and lifestyle factors and the development of prediabetes and diabetes, as well as on mortality. It is unclear how the protective effect of a healthy lifestyle against death differs between individuals with different glucose metabolic profiles and whether PIR mediates this effect. This study aimed to explore whether healthy lifestyle and family PIR reduced the risk of all-cause mortality in participants with different metabolic status and the mediating role of PIR. Subjects and methods In total, 21,411 participants from the 2001–2018 National Health and Nutrition Examination Survey (NHANES) and follow-up until 2019 were included. The weighted healthy lifestyle score was constructed based on smoking, alcohol consumption, physical activity, diet (HEI-2015), and body mass index. Generalized linear regression models were used to analyze the association between healthy lifestyle, PIR, and all-cause mortality. Cox proportional hazard models were used to calculate hazard ratios (HRs) and 95% confidence intervals, Kaplan-Meier survival curve was used to analyze the all-cause mortality associated with PIR and lifestyle. Furthermore, the mediation proportion of PIR in all-cause mortality attributed to healthy lifestyle was analyzed among participants with normal glucose regulation, prediabetes, or diabetes after multivariable adjustment. Results There were significant differences in healthy lifestyle and PIR among people with normal glucose regulation, prediabetes and diabetes. During a mean follow-up of 92 months, participants with prediabetes or diabetes were also likely to have a higher mortality rate, respectively 583 (8.3%) and 263 (12.7%). More than 2 healthy lifestyles were associated with 42% (HR, 0.58; 95% CI, 0.35–0.95) to 76% (HR, 0.24; 95% CI, 0.12–0.44) reduced risk of all-cause mortality among participants with prediabetes, but among those with diabetes, who had ≥ 4 healthy lifestyles were associated with 72% reduced risk of all-cause mortality (HR, 0.28; 95% CI, 0.09–0.90). The middle and high PIR were associated with at least a 37% (HR, 0.63; 95% CI, 0.47–0.83) to 65% (HR, 0.35; 95% CI, 0.18–0.68) lower risk of all-cause mortality in participants with prediabetes and diabetes. Furthermore, PIR mediated 5.81-14.93% and 7.72-10.10% of the association between healthy lifestyle and all-cause mortality among normal glucose regulation and prediabetic participants, respectively. However, the mediating effect of PIR was not significant among diabetic participants. Conclusions Our findings highlight the importance of promoting adherence to a healthy lifestyle and improving PIR in prediabetic patients to reduce the risk of all-cause mortality, and the protective effect is more significant with more healthy lifestyles and higher PIR. This study can help clinicians and health systems develop more targeted treatments for people with different metabolic levels.